[tex]\displaystyle 3x-(x+18)=4(x+3)\\3x-x-18=4x+12\\2x-18=4x+12\\2x-4x=12+18\\-2x=30\\x=-15[/tex]
Ответ:
x=-15
3x-(x+18)=4*(x+3)
3x-x-18=4(x+3)
3x-x-18=4x+12
2x-18=4x+12
2x-18-4x=12
2x-18-4x=12+18
-2x=12+18
-2x=30
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
[tex]\displaystyle 3x-(x+18)=4(x+3)\\3x-x-18=4x+12\\2x-18=4x+12\\2x-4x=12+18\\-2x=30\\x=-15[/tex]
Verified answer
Ответ:
x=-15
3x-(x+18)=4*(x+3)
3x-x-18=4(x+3)
3x-x-18=4x+12
2x-18=4x+12
2x-18-4x=12
2x-18-4x=12+18
-2x=12+18
-2x=30
x=-15